(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article presents an imaginative solution to the most important subject of the day. Engagement of employees is a primary motivating factor for company growth. High levels of participation in domestic and multinational organizations facilitate employee growth, foster client satisfaction and enhance corporate success and profitability for stakeholders. The research identifies the connation between the dedication of workers and revolutionary leadership. The study demonstrates that the idea of employee participation in management colleges, with particular attention to the Indian management climate, is desperately required.This article outlines the need for employee participation in the company and the significance of changes in the development of a culture of organization where employee engagement thrives and flourishes.